Aloe Vera Gel sebagai Body Marker Alternatif untuk Pemeriksaan MRI Pelvis Wanita - Muzhaffar, Muhammad Isfan; Sugiyanto; Kartikasari, Yeti; Fatimah; Latifah, Leny; Wibowo, Gatot Murti (Poltekkes Kemenkes Semarang, 2026)
Background: Pathological conditions of the female pelvis, such as infertility and cancer, are prevalent in Indonesia, with disorders like cervical cancer affecting up to 52% of women. In pelvic MRI exams, ultrasound gel is used to enhance image clarity, but commercial gels may cause allergic reactions or infections. Aloe vera gel, with its natural properties like high water content, pH balance, and anti-inflammatory effects, presents a safer alternative for use in these procedures. Methods: This study used a research and development approach to determine the optimal formulation of aloe vera gel as an alternative body marker for pelvic MRI in women. MRI imaging was performed using T1 and T2 weighted sequences with the pelvic MRI 1,5 T protocol at Telogorejo Hospital, Semarang. Results: Aloe vera gel was formulated by mixing pure aloe vera extract, aquabides, and xanthan gum to mimic the characteristics of ultrasound gel. Two formulations with varying concentrations of xanthan gum were tested. MRI imaging results showed that the gel with a 1:50 ratio of xanthan gum provided the highest signal-to-noise ratio (SNR) for both T1 and T2 weighted images compared to ultrasound gel. Conclusions: Aloe vera gel formulated with xanthan gum at a 1:50 ratio proved to be a suitable alternative to commercial ultrasound gels for pelvic MRI examinations. The gel's high viscosity and bioactive compounds contributed to its stability, enhancing MRI image quality and making it a safer and effective option for use in gynecological imaging procedures.